Economic and psychological effects of latitude - León, Federico R. (2012)
The nations’ wealth and their population’s education increase with distance from the equator. The impact of latitude seen in Peru additionally encompasses women’s fertility desires and domestic power and the general population’s mental health.This article summarizes such findings and assesses the economic theories formulated to explain the latitude-wealth linkage considering temperature and cultural dissemination, as well as evolutionary theories, which point to racial differences in intelligence and personality. The article presents an alternative, recent Peruvian theory based on the contemporary influence of ultraviolet radiation and vitamin D which accounts for the evidence with greater parsimony and has important practical implications.